A conceptual framework for healthy food choice in full-service restaurant. Issue 3 (27th May 2017) - Jin, Naehyun (Paul); Lee, Sang-Mook
ABSTRACT: The reasons for people's food choices are complex and result from the interplay of several influences throughout various contexts. Although research has found that various factors influence people's food choices, investigators have not considered the diverse elements affecting the methods or the procedures that people employ for selecting healthy foods in the context of full-service restaurants. Therefore, the current study was conducted to better comprehend family or casual dining consumers' choices in relation to healthy eating behaviors. This qualitative study purposefully sampled three focus group interviews with three different types of participants (mature, nonmature, and chef/manager) to identify important factors that can encourage people to buy or eat healthy foods when dining at full-service restaurants. Content analysis of 16 interviews revealed three levels of healthy food choice factors that affect customers who want to enjoy healthy foods in full-service restaurants.